Risk Analysis Of Onion Farming - Febri Eugene; Melli Suryanty; Nyanyu Neti Arianti (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2019)
The purpose of this research are to identify the factors that cause the emergence of risk in onion farming based on the perceptions of farmers, to know the level of production, costs, and income of onion farming, determine the level of risk for production, costs, and income of onion farming, and to analyze onion farmers in the face of production risks. The method of determining the location is purposive method and the method of determining respondents is the census method. Data analysis methods are qualitative and quantitative. The results of the study show the average production of onion is 5,747 Kg / MT / Ha, the average farming cost is Rp. 74,515,798 MT / Ha, and the average income is Rp. 69,868,313 MT / Ha. The level of risk for production, costs, and income is included in the low category.